DAYA ANTIBAKTERI EKSTRAK DAUN KEDONDONG BANGKOK (Spondias dulcis Forst.) TERHADAP BAKTERI Enterococcus faecalis Antibacterial Potency of Kedondong Bangkok Leaves Extract (Spondias dulcis Forst.) against Enterococcus faecalis Bacteria - Singgih Harseno; Latief Mooduto; Eric Priyo Prasetyo (Conservative Dentistry Journal, 2016)
Background. The prevalence of endodontic infection after root canal treatment caused by the Enterococcus faecalis bacteria ranged between 24-77%. It is caused by resilience and virulence from Enterococcus faecalis. An alternative  solution have to be done toward irrigation of root canal wall which is effective to kill bacteria. Kedondong Bangkok (Spondias dulcis Forst.) is one of the plants or natural substance potentially as an antibacteria. The antibacterial potencies of Kedondong Bangkok leaves extract (Spondias dulcis Forst.) against Enterococcus faecalis bacteria could be identified by determining Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC). Purpose. This study is aimed to prove antibacterial potencies by identifying Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) of Kedondong Bangkok leaves extract (Spondias dulcis Forst.) against Enterococcus faecalis bacteria. Method. This study is an experimental laboratories through research design of The Post Test Only Control Group Design. Value of MIC and MBC were known by counting the growth of Enterococcus faecalis bacteria by treating the leaves extract of Kedondong Bangkok  with concentration respectively 25%, 22,5%, 20%,17,5%, 15%, and 12,5% on nutrient agar media in CFU/ml. Result. In the concentration 12,5% there are 8.8% bacterial growth and in the concentration 15% there are no bacterial growth. Conclusion. Kedondong Bangkok leaf extract (Spondias dulcis Forst.) has an antibacterial potency against Enterococcus faecalis bacteria. The MIC shows in concentration of 12,5% and the MBC shows in concentration of 15%.